Can FRAX Tool be Used for Determination of Risk Score for Osteoporosis Fractures in a Financially Constrained Society Like Bangladesh? (BIRDEM Medical Journal, 2017)
Background: This study was designed to assess the effectiveness of use of the fracture risk assessment system (FRAX) as risk assessment tool for osteoporosis risk score scale in Bangladeshi subjects and to assess how the results of the tools correlate with each other.Methods: This cross-sectional study was conducted between January 2016 to August 2016. The study population was randomly collected 600 Bangladeshi subjects; who attended outpatient department (OPD) of MARKS Medical College & Hospital, Dhaka, Bangladesh. The age range of the subjects was between 40 to 75 years. The subjects had not done a bone mineral density (BMD) score. None of them were previously diagnosed or got treatment for osteoporosis. A questionnaire was designed to complete the osteoporosis specific risk score sheet. Major osteoporotic and hip fracture incidence to 10-years as a function of the FRAX probability was calculated by using fracture risk assessment system.Results: A total of 600 subjects were included. Among them, 59.2% and 40.8%were male and female respectively. Mean age (Mean ± SD) of the study, subjects were 52.16±7.96 years. Among study subjects, mean BMI was more in females in comparison to males (p